LABORATORY STUDY FOR ANALYZING ROCK TYPING METHOD BASED ON SONIC WAVEFORM DATA - DWI PRIYANTO (NIM : 22211057), AGUS
Accuracy of rock typing process is really important aspect for characterizing reservoir. Common way used for rock typing is based on pore geometry from core analysis product. This research shows the result of laboratory measurement in deriving sonic wave data of synthetic cores to find the way of rock typing method based on sonic wave data. Firstly, 108 of synthetic core were made into three different groups. Each group has different composition that gives different type of rock. Two of them are sandstone with different cement composition and the last group is sandstone combined with bentonite to make a synthetic of shale. There are two main processes of this research. Firstly is to make a rock typing models by plotting porosity and permeability of these synthetic cores and then make another rock typing models from several rock properties based on sonik wave data. So the main idea is transmitting sonic wave to the synthetic core and deriving vp/vs ratio of each group of synthetic core. Porosity and permeability of synthetic core were measured by using PORG-200TM and PermG-200TM and sonic wave was transmitted by using PanametricTM Sonic Wave Transducer. Plotting of porosity and permeability of synthetic core shows separation area for different rock type, but this separation is not clear enough. After transmitting sonic wave into each group of synthetic core, we got travel time of P-wave and S-wave. Several graphs were made by plotting P-wave travel time versus porosity, S-wave travel time versus porosity, Vp versus Vs and Shear modulus versus bulk modulus. These four graphs show very clear separation for different type of synthetic core.